Lack of host specialization despite selective host use in brood parasitic cuckoo catfish - Reichard, Martin; Koblmüller, Stephan; Blažek, Radim; Zimmermann, Holger; Katongo, Cyprian; Bryjová, Anna; Bryja, Josef (Molecular ecology, 2023)
Host-parasite dynamics involve coevolutionary arms races, which may lead to host specialization and ensuing diversification. Our general understanding of the evolution of host specialization in brood parasites is compromised by a restricted focus on bird and insect lineages. The cuckoo catfish (Synodontis multipunctatus) is an obligate parasite of parental care of mouthbrooding cichlids in Lake Tanganyika. Given the ecological and taxonomic diversity of mouthbrooding cichlids in the lake, we hypothesized the existence of sympatric host-specific lineages in the cuckoo catfish. In a sample of 779 broods from 20 cichlid species, we found four species parasitized by cuckoo catfish (with prevalence of parasitism of 2%-18%). All parasitized cichlids were from the tribe Tropheini, maternal mouthbrooders that spawn over a substrate (rather than in open water). Phylogenetic analysis based on genomic (ddRAD sequencing) and mitochondrial (Dloop) data from cuckoo catfish embryos showed an absence of host-specific lineages. This was corroborated by analyses of genetic structure and co-ancestry matrix. Within host species, parasitism was not associated with any individual characteristic we recorded (parent size, water depth), but was costly as parasitized parents carried smaller clutches of their own offspring. We conclude that the cuckoo catfish is an intermediate generalist and discuss costs, benefits and constraints of host specialization in this species and brood parasites in general.
Keywords: Animals; paraziti; cichlidy; Host-Parasite Interactions; interakce hostitele a parazita; Parasites; voda; sumci; Phylogeny; Cichlids; Water; host specialisation; host-parasite relationship; social evolution; brood parasitism; interspecific interactions; hnízdění; fish; zvířata; fylogeneze; Nesting Behavior; Catfishes